Effect of ethanolic extract of Vitex negundo leaves on experimentally induced inflammatory bowel disease in albino rats - Kaushik, Shipra; Wardhan, Harsh; Kaushik, Shobhit; Verma, Vikash (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Ulcerative colitis (UC) and Crohn’s disease (CD) are collectively known as inflammatory bowel disease (IBD). Pathophysiology of IBD is not known with certainty. Immunological processes and reactive oxygen species (ROS) have been proposed to contribute considerably to development of tissue injury. Some of the intestinal and/or colonic injury and dysfunction observed in IBD is due to elaboration of these reactive species. Commonly used drugs, in particular sulfasalazine and its active moiety 5-aminosalicylic acid, are potent ROS scavengers. The present study was carried out to evaluate the effect of ethanolic extract of Vitex negundo (EEVN) leaves on experimentally induced inflammatory bowel disease in albino rats. Methods: The rats were divided into four groups of six animals each. Group A and group B received gum acacia per orally, group C received EEVN in dose of 500 mg/kg/day per orally, and group D received 5-amino salicylic acid (5-ASA) in the dose of 100 mg/kg/day per orally. All the animals were pre-treated with respective drugs (volume of drugs was kept constant at 10 ml/kg) for five days, along with the normal diet. On fifth day animals were kept fasting for 12 hours (overnight) and IBD was induced next morning in Groups B, C and D by administration of one ml of 4% acetic acid solution transrectally (TR). Group A (normal control) received 0.9% normal saline transrectally (TR) instead. Results: The results have been shown that EEVN has significant activity against experimentally induced IBD when compared to the experimental control, with near normalization of colon architecture both macroscopically as well as microscopically. Tissue oxidative stress was reduced with significant improvement in tissue levels of superoxide dismutase (SOD) and catalase (CAT). Also, significant improvement in levels of myeloperoxidase (MPO) was observed. Conclusions: It is concluded that ethanolic extract of leaves of Vitex negundo has got potent activity against experimentally induced IBD due to its anti-inflammatory and anti-oxidant properties.